2013
DOI: 10.1182/blood-2013-02-474437
|View full text |Cite
|
Sign up to set email alerts
|

Cold agglutinin disease

Abstract: Cold agglutinin disease is a rare and poorly understood disorder affecting 15% of patients with autoimmune hemolytic anemia. We reviewed the clinical and pathologic features, prognosis, and management in the literature and describe our institutional experience to improve strategies for accurate diagnosis and treatment. Retrospective analysis identified 89 patients from our institution with cold agglutinin disease from 1970 through 2012. Median age at symptom onset was 65 years (range, 41 to 83 years), whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
334
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(345 citation statements)
references
References 72 publications
4
334
1
6
Order By: Relevance
“…In the study by Swiecicki et al, (7) in which 89 adult patients who were diagnosed as having cold agglutinin disease were evaluated retrospectively, it was reported that more than 90% of the patients had a positive Coombs test with anti-C3. In our patient, the presence of a positive Coombs test with anti-C3, visible agglutination inside the tube when the blood sample was incubated at +4°C, and disappearance of agglutination at room temperature in addition to hemolysis findings supported the diagnosis of cold-antibody AIHA.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Swiecicki et al, (7) in which 89 adult patients who were diagnosed as having cold agglutinin disease were evaluated retrospectively, it was reported that more than 90% of the patients had a positive Coombs test with anti-C3. In our patient, the presence of a positive Coombs test with anti-C3, visible agglutination inside the tube when the blood sample was incubated at +4°C, and disappearance of agglutination at room temperature in addition to hemolysis findings supported the diagnosis of cold-antibody AIHA.…”
Section: Discussionmentioning
confidence: 99%
“…4 Cold agglutinins are produced either in response to infection 5 or by paraneoplastic or neoplastic growth. 6 The most common infectious agents are: Mycoplasma pneumoniae, and infectious mononucleosis. Less commonly, cold agglutinins are associated with other bacterial and viral diseases, such as Cytomegalovirus, Epstein-Barr virus, Legionella, Citrobacter, Influenza, Varicella and Listeria Monocytogenes.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In a large retrospective study, lymphoma was noted in 12% of patients with CAD including indolent B-cell lymphoma and diffuse large cell lymphoma. 24 These patients may have either anti-i or anti-I antibodies, and titer concentration is dependent on the activity of the disease. Management of hemolysis in such patients is primarily dependent on the response of the underlying B-cell neoplasm to treatment.…”
Section: Case Presentationmentioning
confidence: 99%
“…Rituximab has been studied as a single agent as well as in combination with steroids, oral Fludarabine (not available in the United States), and interferon (Table 2). 20,23,24,25 Immunosuppressive agents (e.g. cyclophosphamide or chlorambucil) are used but limited by myelotoxicity.…”
Section: Case Presentationmentioning
confidence: 99%